Narrative-driven immersion and students perceptions in an online software programming course - Fontes, Mario Madureira (2021)
Learning software programming is challenging for software engineering students. In this paper, students’ engagement in learning software engineering programming is considered under the SimProgramming approach using the OC2-RD2 narrative technique to create an immersive learning context. The objectives of this paper are twofold: presenting a narrative-driven immersive learning approach to introduce software engineering concepts and coding techniques to online undergraduate students; and analyzing the students’ feedback on this approach. Thematic analysis of the metacognitive tasks was performed on the students’ fortnightly reflections about their learning progress. Content analysis was based on interest categories, students’ perceptions, metacognitive challenges, narratives, examples and aspects to be kept or to be improved. Data from the content analysis were organized into categories, subcategories, indicators, and recording units and their categorization was peer-reviewed. The narratives were considered by the students as interesting, appealing, akin to professional reality and promoting interaction. Most students thought the approach was helpful for learning software programming.